Sulforaphane Ameliorates Metabolic Changes Associated With Status Epilepticus in Immature Rats - Daněk, Jan; Danačíková, Šárka; Kala, David; Svoboda, Jan; Kapoor, Sonam; Pošusta, Antonín; Folbergrová, Jaroslava; Tauchmannová, Kateřina; Mráček, Tomáš; Otáhal, Jakub (Frontiers in Cellular Neuroscience, 2022)
Status epilepticus (SE) is a common paediatric emergency with the highest incidence in the neonatal period and is a well-known epileptogenic insult. As previously established in various experimental and human studies, status epilepticus induces long-term alterations to brain metabolism, alterations which directly contribute to the development of epilepsy. To influence these changes, organic isothiocyanate compound sulforaphane (SFN) has been used in the present study for its known effect of enhancing antioxidative, cytoprotective, and metabolic cellular properties via the Nrf2 pathway. We have explored the effect of SFN in a model of acquired epilepsy induced by Li Cl Pilocarpine in immature rats (12 days old). Energy metabolites PCr, ATP, glucose, glycogen, and lactate were determined by enzymatic fluorimetric methods during the acute phase of status epilepticus. Protein expression was evaluated by Western blot analysis. Neuronal death was scored on FluoroJadeB stained brain sections harvested 24h after SE. To assess the effect of SFN on glucose metabolism we have performed series of 18F-DG µCT/PET recordings 1h, 1 day, and 3 weeks after the induction of status epilepticus. Responses of cerebral blood flow to electrical stimulation and their influencing by SFN were evaluated by laser Doppler flowmetry. We have demonstrated that the Nrf2 pathway is upregulated in the CNS of immature rats after SFN treatment. In the animals who had undergone SE, SFN was responsible for lowering glucose uptake in most regions 1 hour after the induction of SE. Moreover, SFN partially reversed hypometabolism observed after 24 hours and achieved full reversal ~3 weeks after SE. Since no difference in cell death was observed in SFN treated group these changes cannot be attributed to differences in neurodegeneration. SFN per se did not affect the glucose uptake at any given time point suggesting that SFN improves endogenous CNS ability to adapt to the epileptogenic insult. Furthermore, we had discovered that SFN improves blood flow and accelerates CBF response to electrical stimulation. Our findings suggest that SFN improves metabolic changes induced by SE which have been identified during epileptogenesis in various animal models of acquired epilepsy.